(untitled) (Revista Brasileira de Contabilidade e Gestão, 2017)
It is observed a considerable increase in the Brazilian scientific production in the accounting area, in search of scientific knowledge part of the scientific research for a later disclosure. In this context, it aims to investigate the profile of publications in the six editions of the UFSC Congress of Scientific Initiation in Accounting, which were carried out from 2007 to 2015. A methodology for predominantly quantitative, descriptive and bibliometric. The research population includes all 314 articles published in the Congressional record. Among the main findings highlight the predominance of articles two and three authors, the Federal University of Santa Catarina (UFSC) was the most prolific institution with 104 papers presented, followed by the Federal University of Uberlândia (UFU) with 46 articles. Also in relation to the results, the maximum degree of the authors was to graduate and doctorate and the most productive authors are Edvalda Araújo Leal (UFU) and Sandra Rolim Ensslin (UFSC) both published 11 articles. The most widely used approach was qualitative (119) with respect to the problem and descriptive (169) related to the goal and the Public Accounts Government was the sub theme choicest (26 articles). The conclusion of this research is that there are several issues in accounting to be explored by future researchers, advancing the scientific production and dissemination of knowledge.